2010
DOI: 10.4028/www.scientific.net/amr.163-167.184
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Eccentric Compressive Performance of Steel Tube-Reinforced Concrete Column

Abstract: Eccentric loading experiment of 13 steel tube-reinforced concrete columns and a reinforced concrete column is implemented. The whole process from the start load on the steel tube-reinforced concrete column until damage has been researched. Change of ultimate bearing capacity with eccentricity, longitudinal reinforcement ratio, position coefficient has been studied, and deflection curve and load-vertical displacement curve under eccentric compressive load were obtained. Failure characteristics of steel tube-rei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The behavior of CECFST short columns loaded eccentrically to failure was ascertained by Guo et al 46–47 and An et al 48 experimentally. It was reported that the ductility and ultimate strength of CECFST columns were markedly reduced by increasing the eccentricity ratio.…”
Section: Introductionmentioning
confidence: 98%
“…The behavior of CECFST short columns loaded eccentrically to failure was ascertained by Guo et al 46–47 and An et al 48 experimentally. It was reported that the ductility and ultimate strength of CECFST columns were markedly reduced by increasing the eccentricity ratio.…”
Section: Introductionmentioning
confidence: 98%
“…Han and An [13] studied the performance of concrete-encased CFST columns under axial compression by tests, and three types of simplified ultimate strength formulae were built. An and Han [14] and Guo et al [15] conducted tests on concrete-encased CFST columns under combined compression and bending, and the cross-sectional bending capacity formulae were proposed, respectively. Han et al [16] tested nine concreteencased CFST columns under constant axial load and cyclically increasing flexural loading and pointed out that the columns exhibited good energy dissipation and ductility.…”
Section: Introductionmentioning
confidence: 99%